CD137+CD154− Expression As a Regulatory T Cell (Treg)-Specific Activation Signature for Identification and Sorting of Stable Human Tregs from In Vitro Expansion Cultures - Nowak, Anna; Lock, Dominik; Bacher, Petra; Hohnstein, Thordis; Vogt, Katrin; Gottfreund, Judith; Giehr, Pascal; Polansky, Julia K.; Sawitzki, Birgit; Kaiser, Andrew; Walter, Jörn; Scheffold, Alexander (Frontiers in Immunology, 2018)
Regulatory T cells (Treg) are an attractive therapeutic tool for several different immune pathologies. Therapeutic Treg application often requires prolonged in vitro culture to generate sufficient Treg numbers or to optimize their functionality, e.g. via genetic engineering of their antigen receptors. However, purity of clinical Treg expansion cultures is highly variable and it is currently impossible to identify and separate stable Tregs from contaminating effector T cells (Teff), either ex vivo or after prior expansion. This represents a major obstacle for quality assurance of expanded Tregs and raises significant safety concerns. Here, we describe a Treg activation signature that allows identification and sorting of epigenetically imprinted Tregs even after prolonged in vitro culture. We show that short-term reactivation resulted in expression of CD137 but not CD154 on stable FoxP3+ Tregs that displayed a demethylated TSDR, high suppressive potential and lack of inflammatory cytokine expression. We also applied this Treg activation signature for rapid testing of chimeric antigen receptor (CAR) functionality in human Tregs and identified major differences in the signaling requirements regarding CD137 versus CD28 co-stimulation. Taken together, CD137+CD154- expression emerges as a universal Treg activation signature ex vivo and upon in vitro expansion allowing the identification and isolation of epigenetically stable antigen-activated Tregs and providing a means for their rapid functional testing in vitro.